Method for producing garnet-type oxide solid electrolyte

Through pressurized forming, heating and cooling and organic ion plastic crystal contacting processes, the lithium carbonate problem of garnet oxide solid electrolyte surface is solved, the ion conductivity and interface resistance are improved, and the electrolyte manufacturing in various shapes is adapted.

CN120266226APending Publication Date: 2025-07-04JTEKT CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280102128.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-07-04

Smart Images

  • Figure CN120266226A_ABST
    Figure CN120266226A_ABST
Patent Text Reader

Abstract

A method for producing a garnet-type oxide solid electrolyte, in which a Li7La3Zr2O12 powder having a median diameter (D50) of 0.02-0.2 [mu] m is press-molded to obtain an intermediate, the intermediate is heated at 1050-1150 DEG C for 1-3 hours, and then cooled to room temperature within 1 hour to obtain a first garnet-type oxide solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for manufacturing a garnet-type oxide solid electrolyte. Background Art

[0002] In recent years, all-solid-state batteries have been proposed as next-generation batteries for automobiles and electronic devices. An all-solid-state battery is a secondary battery in which a solid electrolyte is interposed between a positive electrode and a negative electrode. As the solid electrolyte used in an all-solid-state battery, a sulfide-based solid electrolyte and an oxide-based solid electrolyte are known. Generally, a sulfide-based solid electrolyte is softer than an oxide-based solid electrolyte, and thus has a low interfacial resistance and a high ionic conductivity. However, a sulfide-based solid electrolyte has lower chemical stability than an oxide-based solid electrolyte, and when it comes into contact with the atmosphere, hydrogen sulfide gas is generated. On the other hand, an oxide-based solid electrolyte has higher chemical stability than a sulfide-based solid electrolyte, but is hard, so it is difficult to reduce the interfacial resistance and the ionic conductivity is low.

[0003] The oxide-based solid electrolyte includes perovskite-type La 1-3x Li 3x TiO3, NASICON-type Li 1+x Al x Ti 2-x (PO4)3, garnet-type Li7La3Zr2O 12 (hereinafter sometimes referred to as "LLZO"), etc. LLZO has high stability with respect to lithium metal and is expected to be used as an oxide-based solid electrolyte for all-solid-state batteries. However, LLZO has a property of easily forming lithium carbonate on its surface. The lithium carbonate formed on the surface of LLZO increases the interfacial resistance of the garnet-type oxide solid electrolyte. The increase in the interfacial resistance causes a decrease in the ionic conductivity. In addition, Patent Document 1 discloses a method for reducing the interfacial resistance by grinding a garnet-type oxide solid electrolyte to remove lithium carbonate formed on the surface.

[0004] Prior Art Documents

[0005] Patent Documents

[0006] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2020-205284 Summary of the Invention

[0007] In the method for manufacturing a garnet-type oxide solid electrolyte according to one aspect of the present disclosure, Li7La3Zr2O having a median particle diameter (D50) of 0.02 to 0.2 μm is used. 12The (LLZO) powder is press-formed to obtain an intermediate, and the intermediate is heated at 950 to 1050 °C for 1 to 3 hours, and then cooled to room temperature within 1 hour to obtain a first garnet-type oxide solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 It is a graph showing the relationship between the heating temperature and the ionic conductivity in the heating and cooling process where the cooling time of the garnet-type oxide solid electrolyte made of LLZO powder with different median particle sizes (D50) is 4 hours (4 hours or more).

[0009] Figure 2 It is a graph showing the relationship between the heating temperature and the ionic conductivity in the heating and cooling process where the cooling time of the garnet-type oxide solid electrolyte made of LLZO powder with different median particle sizes (D50) is 1 hour (1 hour or less). DETAILED DESCRIPTION

[0010] <The technical problem to be solved by the invention of the present disclosure>

[0011] As described above, the ionic conductivity of the oxide-based solid electrolyte is lower than that of the sulfide-based solid electrolyte. In addition, the ionic conductivity of the garnet-type oxide solid electrolyte is reduced due to lithium carbonate or the like formed on the surface. Therefore, a method for manufacturing a garnet-type oxide solid electrolyte with high ionic conductivity is required.

[0012] The method disclosed in Patent Document 1 is a method for improving the ionic conductivity of the garnet-type oxide solid electrolyte by removing lithium carbonate formed on the surface of the garnet-type oxide solid electrolyte through a grinding process. However, it is difficult to apply the grinding method described in Patent Document 1 to the garnet-type oxide solid electrolyte having undulations on the surface. Therefore, when applying the above grinding treatment, the shape of the garnet-type oxide solid electrolyte to be manufactured is limited. Therefore, a method for manufacturing a garnet-type oxide solid electrolyte that can easily remove impurities such as lithium carbonate for various shapes of garnet-type oxide solid electrolytes is required.

[0013] <The effects of the invention of the present disclosure>

[0014] According to the invention of the present disclosure, there is provided a method for manufacturing a garnet-type oxide solid electrolyte that can easily adapt to various shapes of garnet-type oxide solid electrolytes and can manufacture a garnet-type oxide solid electrolyte with high ionic conductivity.

[0015] <Outline of the embodiments of the invention of the present disclosure>

[0016] Hereinafter, the outline of the embodiments of the invention of the present disclosure will be listed and described.

[0017] (1) In the method for manufacturing a garnet-type oxide solid electrolyte of the present disclosure, Li7La3Zr2O with a median particle size (D50) of 0.02 to 0.2 μm 12 (LLZO) powder is press-molded to obtain an intermediate, and the above intermediate is heated at 1050 to 1150 °C for 1 to 3 hours, and then cooled to room temperature within 1 hour to obtain a first garnet-type oxide solid electrolyte.

[0018] The manufacturing method described in the above (1) can manufacture garnet-type oxide solid electrolytes of various shapes with high ionic conductivity.

[0019] (2) In the manufacturing method described in the above (1), at least one selected from organic ionic plastic crystals and ionic liquids is brought into contact with the above first garnet-type oxide solid electrolyte to obtain a second garnet-type oxide solid electrolyte.

[0020] The manufacturing method described in the above (2) can manufacture a second garnet-type oxide solid electrolyte with higher ionic conductivity.

[0021] (3) In the manufacturing method described in the above (1) or (2), the above LLZO powder is press-molded under the condition of 72 MPa or more to obtain the above intermediate.

[0022] The manufacturing method described in the above (3) can sufficiently ensure the hardness of the intermediate, and thus can maintain the shape of the intermediate.

[0023] <Details of the embodiments of the invention of the present disclosure>

[0024] Hereinafter, embodiments of the present disclosure will be described.

[0025] It should be noted that in the present disclosure, the embodiments of the invention should be considered illustrative in all aspects and not restrictive. The scope of the present invention is shown by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims.

[0026] The method for manufacturing a garnet-type oxide solid electrolyte of the present disclosure includes:

[0027] 1) A press-molding step in which Li7La3Zr2O with a median particle size (D50) of 0.02 to 0.2 μm 12 (LLZO) powder is press-molded to obtain an intermediate;

[0028] 2) A heating and cooling step in which the above intermediate is heated at 1050 to 1150 °C for 1 to 3 hours, and then cooled to room temperature within 1 hour to obtain a first garnet-type oxide solid electrolyte.

[0029] Further, there is a 3) contacting step in which at least one selected from organic ionic plastic crystals and ionic liquids is brought into contact with the above-mentioned first garnet-type oxide solid electrolyte to obtain a second garnet-type oxide solid electrolyte. Hereinafter, the above-mentioned 1) pressing and forming step, 2) heating and cooling step, and 3) contacting step will be described in sequence.

[0030] 1) Pressing and forming step

[0031] First, in the method for manufacturing a garnet-type oxide solid electrolyte of the present disclosure, an LLZO powder having a median particle diameter (D50) of 0.02 to 0.2 μm is press-formed to obtain an intermediate. The median particle diameter (D50) is a value measured by the laser diffraction / scattering method in accordance with JIS Z 8825:2013.

[0032] The above-mentioned LLZO powder having a median particle diameter (D50) of 0.02 to 0.2 μm can be a commercially available LLZO powder, or can be an LLZO powder prepared by pulverizing an LLZO powder having a median particle diameter (D50) exceeding 0.2 μm into the above-mentioned specified median particle diameter. Here, the pulverization method of the LLZO powder may use a known method and is not particularly limited. Examples of the specific pulverization method include pulverization methods using a bead mill, a ball mill, a jet mill, etc. The above-mentioned LLZO powder having a specified median particle diameter can be obtained, for example, by removing isopropanol from an isopropanol suspension obtained by pulverizing a commercially available LLZO powder having a median particle diameter (D50) exceeding 0.2 μm in isopropanol using a bead mill with an evaporator.

[0033] The above-mentioned pressing and forming may be carried out by a known pressing and forming that can be used in the manufacture of solid electrolytes, and there is no particular limitation. An example of a process including a known pressing and forming step is a step of uniaxially pressing and forming by putting the above-mentioned LLZO powder having a specified median particle diameter into a powder former and then using a hydraulic press. In the above-mentioned uniaxial pressing and forming, the pressure when obtaining the intermediate of the above-mentioned LLZO powder is preferably 72 MPa or more. The intermediate obtained by pressing and forming under the condition of 72 MPa or more has sufficient hardness. The pressure when obtaining the intermediate of the above-mentioned LLZO powder may be a high pressure. The upper limit of the pressure when obtaining the intermediate of the above-mentioned LLZO powder is limited by the upper limit that can be pressurized by the pressurizing device used for the above-mentioned hydraulic press, for example, 650 MPa, but may also be 650 MPa or more. Thus, the shape of the intermediate is maintained by the subsequent heating and cooling step and contacting step described below.

[0034] 2) Heating and cooling step

[0035] In the method for manufacturing a garnet-type oxide solid electrolyte of the present disclosure, the above intermediate is heated at 1050 to 1150 °C for 1 to 3 hours, and then cooled to room temperature within 1 hour to obtain a first garnet-type oxide solid electrolyte. The heating in the heating and cooling process can be carried out using a well-known firing furnace used in the manufacture of solid electrolytes. It should be noted that the treatment of the above intermediate at 1050 to 1150 °C for 1 to 3 hours is a treatment for removing impurities such as lithium carbonate and lithium hydroxide present in the above intermediate.

[0036] The heating temperature in the above heating and cooling process is 1050 to 1150 °C. In addition, the heating time in the above heating and cooling process is 1 to 3 hours. Here, the heating temperature being 1050 °C or higher and the heating time being 1 hour or longer are related to sufficiently removing impurities from the intermediate of the above LLZO powder. The heating temperature being 1150 °C or lower and the heating time being 3 hours or shorter can suppress the energy consumption caused by continuous heating, and thus are related to reducing the manufacturing cost of the manufacturing method of the present invention.

[0037] The intermediate of the above heat-treated LLZO powder is cooled to room temperature within 1 hour, thereby becoming a first garnet-type oxide solid electrolyte. Here, the room temperature is 5 to 35 °C. The above cooling is carried out, for example, by the following method: taking out the intermediate of the heat-treated LLZO powder from the firing furnace and placing it in the drying chamber or glove box described below, thereby reducing its temperature to room temperature within 1 hour. The first garnet-type oxide solid electrolyte obtained by the manufacturing method of the present disclosure including a heating and cooling process having a combination of the above heating temperature, heating time, and the above cooling time has high ionic conductivity.

[0038] 3) Contact process

[0039] The method for manufacturing the second garnet-type oxide solid electrolyte of the present disclosure is a method of obtaining the second garnet-type oxide solid electrolyte by bringing at least one selected from organic ionic plastic crystals and ionic liquids (hereinafter sometimes referred to as "organic ionic plastic crystals, etc.") into contact with the above-mentioned first garnet-type oxide solid electrolyte. The above-mentioned organic ionic plastic crystals, etc. can form an ion conduction path. Therefore, by bringing the above-mentioned organic ionic plastic crystals, etc. into contact with the first garnet-type oxide solid electrolyte, the internal resistance and interface resistance of the second garnet-type oxide solid electrolyte become in a reduced state. In addition, by bringing the above-mentioned organic ionic plastic crystals, etc. into contact with the first garnet-type oxide solid electrolyte, the second garnet-type oxide solid electrolyte becomes a state covered with the above-mentioned organic ionic plastic crystals, etc. Thereby, the formation of lithium carbonate on the surface of the first garnet-type oxide solid electrolyte can be suppressed. As a result, the second garnet-type oxide solid electrolyte is a garnet-type oxide solid electrolyte with high ionic conductivity. It should be noted that from the viewpoint of covering the surface of the above-mentioned first garnet-type oxide solid electrolyte, it is preferable to bring the above-mentioned organic ionic plastic crystals into contact. Bringing the above-mentioned organic ionic plastic crystals into contact with the first garnet-type oxide solid electrolyte helps to obtain a second garnet-type oxide solid electrolyte with higher ionic conductivity.

[0040] Regarding the method for obtaining the contact between the above-mentioned first garnet-type oxide solid electrolyte and the above-mentioned organic ionic plastic crystals, etc., any method that can impregnate the above-mentioned organic ionic plastic crystals, etc. into the first garnet-type oxide solid electrolyte is acceptable and there is no particular limitation. Examples of the method for obtaining the above contact include a method of immersing the first garnet-type oxide solid electrolyte in the above-mentioned organic ionic plastic crystals, etc., or a method of dropping the above-mentioned organic ionic plastic crystals, etc. into the first garnet-type oxide solid electrolyte.

[0041] The above-mentioned organic ionic plastic crystals may be any known organic ionic plastic crystals that can be applied to lithium secondary batteries without particular limitation. Examples of the above-mentioned organic ionic plastic crystals include aliphatic quaternary ammonium salts containing perfluoro anions, such as N,N-diethyl-N-methyl-N-propylammonium trifluoromethyltrifluoroborate (N 2,2,1,3 [BF3CF3]) analogs, N-ethyl-N-methyl-pyrrolidine bis(fluorosulfonyl)amide (Py 1,2 [FSA]) analogs, etc. It should be noted that from the viewpoint of electrochemical stability, the above-mentioned organic ionic plastic crystals are preferably N 2,2,1,3 [BF3CF3].

[0042] The above-mentioned ionic liquids may be any known ionic liquids that can be applied to lithium secondary batteries without particular limitation. Examples of the above-mentioned ionic liquids include N-methyl-N-propylpyrrolidine bis(fluorosulfonyl)amide (Py1,3 [FSA]), N-methyl-N-propylpyrrolidine Bis(trifluoromethylsulfonyl)amide (Py 1,3 [TFSA]), N-ethyl-N-methylimidazole Bis(fluorosulfonyl)amide ([EMI][FSA]). It should be noted that from the perspective of electrochemistry, the above ionic liquids preferably Py 1,3 [FSA].

[0043] Each process in the method for manufacturing the garnet-type oxide solid electrolyte of the present disclosure can be carried out in a drying chamber or a glove box. It is particularly preferred to carry out the above heating and cooling processes and contact processes in a drying chamber. Thereby, the formation of lithium carbonate and lithium hydroxide on the surface of the first garnet-type oxide solid electrolyte due to the reaction of the first garnet-type oxide solid electrolyte with carbon dioxide and water can be suppressed. The environment in the above drying chamber and glove box is preferably a dew point of -50°C or lower.

[0044] Examples

[0045] Next, the invention of the present disclosure will be further described in detail based on examples, but the invention of the present disclosure is not limited to the examples.

[0046] 1. Use of raw materials

[0047] (LLZO powder)

[0048] · LLZO powder, median particle size (D50) 0.1 μm, product A

[0049] · LLZO powder, median particle size (D50) 0.1 μm, product B

[0050] · LLZO powder, median particle size (D50) 1 μm, product (manufactured by Toyoshima Seisakusho Co., Ltd.)

[0051] · LLZO powder, median particle size (D50) 10 μm, product (manufactured by Toyoshima Seisakusho Co., Ltd.)

[0052] (Obtaining of LLZO powder, median particle size (D50) 0.1 μm, product A)

[0053] The LLZO isopropanol suspension was prepared by pulverizing LLZO powder, median particle size (D50) 8.9 μm, product (manufactured by Daiichi Rare Element Chemical Industry Co., Ltd.) in isopropanol using a bead mill (Easynano (RMB type) (manufactured by Aimex Co., Ltd.)) with a ZrO2 medium particle size of φ0.1 mm. The LLZO powder, median particle size (D50) 0.1 μm, product A was obtained by removing isopropanol from the LLZO isopropanol suspension using an evaporator.

[0054] (Obtaining LLZO powder with median particle size (D50) of 0.1 μm, Product B)

[0055] The LLZO isopropanol suspension was prepared by pulverizing the above-mentioned LLZO powder with a median particle size (D50) of 1 μm (manufactured by Toyoshima Seisakusho Co., Ltd.) in isopropanol using a bead mill (Easynano (RMB type) (manufactured by Aimex Co., Ltd.)) with a ZrO2 medium particle size of φ0.1 mm. Product B of LLZO powder with a median particle size (D50) of 0.1 μm was obtained by removing isopropanol from the LLZO isopropanol suspension using an evaporator.

[0056] 2. Pressing and forming process

[0057] 1) Obtaining Intermediate 1

[0058] Intermediate 1 was obtained as follows: In a drying chamber with a dew point of -50°C or lower, 0.075 to 0.15 g of Product A of LLZO powder with a median particle size (D50) of 0.1 μm was put into a powder forming mold with an inner diameter of 10 mm, and then the LLZO powder with a median particle size (D50) of 0.1 μm was uniaxially pressed and formed at 433 MPa using a hydraulic press. The diameter of Intermediate 1 is 10 mm.

[0059] 2) Obtaining Intermediate 2

[0060] Intermediate 2 was manufactured using Product B of LLZO powder with a median particle size (D50) of 0.1 μm. Regarding Intermediate 2, except for using Product B of LLZO powder with a median particle size (D50) of 0.1 μm instead of Product A of LLZO powder with a median particle size (D50) of 0.1 μm, it was obtained by treating in the same manner as the above-mentioned method for obtaining Intermediate 1. The diameter of Intermediate 2 is 10 mm.

[0061] 3) Obtaining Intermediate 3

[0062] Intermediate 3 was manufactured using Product of LLZO powder with a median particle size (D50) of 1 μm. Regarding Intermediate 3, except for using Product of LLZO powder with a median particle size (D50) of 1 μm instead of Product A of LLZO powder with a median particle size (D50) of 0.1 μm, it was obtained by treating in the same manner as the above-mentioned method for obtaining Intermediate 1. The diameter of Intermediate 3 is 10 mm.

[0063] 4) Obtaining Intermediate 4

[0064] The intermediate 4 is manufactured using LLZO powder with a median particle size (D50) of 10 μm. Regarding the intermediate 4, except for using LLZO powder with a median particle size (D50) of 10 μm instead of LLZO powder with a median particle size (D50) of 0.1 μm product A, it is obtained by treating in the same manner as the method for obtaining the above-mentioned intermediate 1. The diameter of the intermediate 4 is 10 mm.

[0065] 3. Heating and Cooling Process

[0066] 1) Obtaining the First Garnet-Type Oxide Solid Electrolyte 1

[0067] The first garnet-type oxide solid electrolyte 1 is obtained by treating the above-mentioned intermediate 1 under the conditions in the above-mentioned drying chamber using a firing furnace by the method described in "Effect of Heating Temperature on Ionic Conductivity when Cooling Time is 4 Hours (4 Hours or More)" and "Effect of Heating Temperature on Ionic Conductivity when Cooling Time is 1 Hour (1 Hour or Less)". The diameter of the first garnet-type oxide solid electrolyte 1 is 10 mm.

[0068] 2) Obtaining the First Garnet-Type Oxide Solid Electrolyte 2

[0069] The first garnet-type oxide solid electrolyte 2 is manufactured using the above-mentioned intermediate 2. Regarding the first garnet-type oxide solid electrolyte 2, except for using the above-mentioned intermediate 2, it is obtained by treating by the method described in "Effect of Heating Temperature on Ionic Conductivity when Cooling Time is 1 Hour (1 Hour or Less)" in "Obtaining the Garnet-Type Oxide Solid Electrolyte 1" above. The diameter of the first garnet-type oxide solid electrolyte 2 is 10 mm.

[0070] 3) Obtaining the First Garnet-Type Oxide Solid Electrolyte 3

[0071] The first garnet-type oxide solid electrolyte 3 is manufactured using the above-mentioned intermediate 3. Regarding the first garnet-type oxide solid electrolyte 3, except for using the above-mentioned intermediate 3, it is obtained by treating by the same method as "Obtaining the Garnet-Type Oxide Solid Electrolyte 1" above. The diameter of the first garnet-type oxide solid electrolyte 3 is 10 mm.

[0072] 4) Obtaining the First Garnet-Type Oxide Solid Electrolyte 4

[0073] The first garnet-type oxide solid electrolyte 4 is manufactured using the above-mentioned intermediate 4. Regarding the first garnet-type oxide solid electrolyte 4, in addition to using the above-mentioned intermediate 4, it is obtained by treating using the method described in the "influence of heating temperature on ionic conductivity when the cooling time is 4 hours (4 hours or more)" in the "obtaining of garnet-type oxide solid electrolyte 1" mentioned above. The diameter of the first garnet-type oxide solid electrolyte 4 is 10 mm.

[0074] 4. Measurement of Ionic Conductivity

[0075] To measure the ionic conductivity, a Li symmetric cell 1 using the first garnet-type oxide solid electrolyte 1 was manufactured. Inside the Li symmetric cell 1, the first garnet-type oxide solid electrolyte 1 was clamped between two lithium disks (diameter 8 - 9 mm) with a pressure of approximately 1.5 N·m. The measurement of ionic conductivity was carried out by the AC impedance method. The conditions for AC impedance measurement were an amplitude of 10 - 100 mV and a scanning frequency of 32 MHz - 10 μHz. The Li symmetric cell 2 was manufactured using the first garnet-type oxide solid electrolyte 2. Regarding the Li symmetric cell 2, except for using the first garnet-type oxide solid electrolyte 2 instead of the first garnet-type oxide solid electrolyte 1, it was manufactured by the same treatment as the Li symmetric cell 1. The Li symmetric cell 3 was manufactured using the first garnet-type oxide solid electrolyte 3. Regarding the Li symmetric cell 3, except for using the first garnet-type oxide solid electrolyte 3 instead of the first garnet-type oxide solid electrolyte 1, it was manufactured by the same treatment as the Li symmetric cell 1. The Li symmetric cell 4 was manufactured using the first garnet-type oxide solid electrolyte 4. Regarding the Li symmetric cell 4, except for using the first garnet-type oxide solid electrolyte 4 instead of the first garnet-type oxide solid electrolyte 1, it was manufactured by the same treatment as the Li symmetric cell 1. Regarding the ionic conductivities of the first garnet-type oxide solid electrolyte 2, the first garnet-type oxide solid electrolyte 3, and the first garnet-type oxide solid electrolyte 4, using the Li symmetric cell 2, the Li symmetric cell 3, and the Li symmetric cell 4 instead of the Li symmetric cell 1, the measurement was carried out by the same measurement method as the above-mentioned first garnet-type oxide solid electrolyte 1.

[0076] 5. Influence of Heating Temperature on Ionic Conductivity when the Cooling Time is 4 Hours (4 Hours or More)

[0077] 1) Obtaining of the first garnet-type oxide solid electrolyte 1 (4 hours or more) with different heating temperatures when the cooling time is 1 hour (4 hours or more)

[0078] The first garnet-type oxide solid electrolyte 1 (at 800 °C for 4 hours or more) is obtained through the following heating and cooling process: For intermediate 1, under the conditions in the above drying chamber, it is processed using a firing furnace at a heating temperature of 800 °C and a heating time of 2 hours, and then cooled to room temperature within the furnace of the firing furnace in 4 hours. The first garnet-type oxide solid electrolyte 1 (at 900 °C for 4 hours or more) is obtained through the following heating and cooling process: For intermediate 1, under the conditions in the above drying chamber, it is processed using a firing furnace at a heating temperature of 900 °C and a heating time of 2 hours, and then cooled to room temperature within the furnace of the firing furnace in 4 hours. The first garnet-type oxide solid electrolyte 1 (at 1000 °C for 4 hours or more) is obtained through the following heating and cooling process: For intermediate 1, under the conditions in the above drying chamber, it is processed using a firing furnace at a heating temperature of 1000 °C and a heating time of 2 hours, and then cooled to room temperature within the furnace of the firing furnace in 4 hours. The first garnet-type oxide solid electrolyte 1 (at 1100 °C for 4 hours or more) is obtained through the following heating and cooling process: For intermediate 1, under the conditions in the above drying chamber, it is processed using a firing furnace at a heating temperature of 1100 °C and a heating time of 2 hours, and then cooled to room temperature within the furnace of the firing furnace in 4 hours.

[0079] 2) Obtaining garnet-type oxide solid electrolytes 3 (for 4 hours or more) and 4 (for 4 hours or more) with different heating temperatures when the cooling time is 4 hours (4 hours or more)

[0080] By using intermediate 3, except using intermediate 3 instead of intermediate 1, and using the same method as the above "obtaining garnet-type oxide solid electrolytes 1 with different heating temperatures when the cooling time is 4 hours (4 hours or more)", the first garnet-type oxide solid electrolytes 3 (at 800 °C for 4 hours or more), the first garnet-type oxide solid electrolytes 3 (at 900 °C for 4 hours or more), the first garnet-type oxide solid electrolytes 3 (at 1000 °C for 4 hours or more), and the first garnet-type oxide solid electrolytes 3 (at 1100 °C for 4 hours or more) with different heating temperatures are obtained. Similarly, by using intermediate 4, the first garnet-type oxide solid electrolytes 4 (at 800 °C for 4 hours or more), the first garnet-type oxide solid electrolytes 4 (at 900 °C for 4 hours or more), the first garnet-type oxide solid electrolytes 4 (at 1000 °C for 4 hours or more), and the first garnet-type oxide solid electrolytes 4 (at 1100 °C for 4 hours or more) with different heating temperatures are obtained.

[0081] 3) Confirming the influence of the heating temperature on the ionic conductivity when the cooling time is 4 hours (4 hours or more)

[0082] Figure 1 These are the measurement results of the ionic conductivities of the first garnet-type oxide solid electrolytes 1 (4 hours or more), 3 (4 hours or more), and 4 (4 hours or more) with different heating temperatures when the cooling time is 4 hours (4 hours or more). According to Figure 1 As can be seen, between the heating temperatures of 800 to 1000 °C, the ionic conductivities of the first garnet-type oxide solid electrolytes 1 (4 hours or more), 3 (4 hours or more), and 4 (4 hours or more) tend to increase. However, starting from a heating temperature of 1000 °C or higher, the first garnet-type oxide solid electrolyte 1 (4 hours or more) is different from the first garnet-type oxide solid electrolytes 3 (4 hours or more) and 4 (4 hours or more), and the ionic conductivity decreases. Moreover, the experimental results show that at a heating temperature of 1100 °C, the ionic conductivity of the first garnet-type oxide solid electrolyte 1 (4 hours or more) (about 6.0×10 -5 S / cm) is significantly lower than the ionic conductivity of the first garnet-type oxide solid electrolyte 3 (4 hours or more) (about 1.2×10 -4 S / cm) and the ionic conductivity of the first garnet-type oxide solid electrolyte 4 (4 hours or more) (about 9.0×10 -5 S / cm).

[0083] 6. Influence of heating temperature on ionic conductivity when the cooling time is 1 hour (within 1 hour)

[0084] 1) Obtaining of the first garnet-type oxide solid electrolyte 1 (within 1 hour) with different heating temperatures when the cooling time is 1 hour (within 1 hour)

[0085] Except for setting the cooling time to 1 hour (within 1 hour) instead of 4 hours (4 hours or more), by using the same method as the above-mentioned "obtaining of the first garnet-type oxide solid electrolyte 1 with different heating temperatures when the cooling time is 4 hours (4 hours or more)", the first garnet-type oxide solid electrolyte 1 (800 °C, within 1 hour), the first garnet-type oxide solid electrolyte 1 (900 °C, within 1 hour), the first garnet-type oxide solid electrolyte 1 (1000 °C, within 1 hour), and the first garnet-type oxide solid electrolyte 1 (1100 °C, within 1 hour) with different heating temperatures were obtained.

[0086] 2) Obtaining of the garnet-type oxide solid electrolytes 2 (within 1 hour) and 3 (within 1 hour) with different heating temperatures when the cooling time is 1 hour (within 1 hour)

[0087] By using intermediate 2, except for using intermediate 2 instead of intermediate 1, the same method as that for obtaining garnet-type oxide solid electrolyte 1 with different heating temperatures when the cooling time is 1 hour (within 1 hour) was used to obtain first garnet-type oxide solid electrolytes 2 with different heating temperatures (800 °C, within 1 hour), first garnet-type oxide solid electrolytes 2 (900 °C, within 1 hour), first garnet-type oxide solid electrolytes 2 (1000 °C, within 1 hour), and first garnet-type oxide solid electrolytes 2 (1100 °C, within 1 hour). Similarly, by using intermediate 3, first garnet-type oxide solid electrolytes 3 with different heating temperatures (800 °C, within 1 hour), first garnet-type oxide solid electrolytes 3 (900 °C, within 1 hour), first garnet-type oxide solid electrolytes 3 (1000 °C, within 1 hour), and first garnet-type oxide solid electrolytes 3 (1100 °C, within 1 hour) were obtained.

[0088] 3) Confirmation of the influence of the heating temperature on the ionic conductivity when the cooling time is 1 hour (within 1 hour)

[0089] Figure 2 are the measurement results of the ionic conductivities of the first garnet-type oxide solid electrolytes 1 to 3 with the above different heating temperatures when the cooling time is 1 hour (within 1 hour). According to Figure 2 it can be seen that when the heating temperatures are 800 and 900 °C, the first garnet-type oxide solid electrolytes 1 to 3 show a roughly equal increase in ionic conductivity. On the other hand, it can be seen that starting from a heating temperature of 1000 °C or higher, the ionic conductivities of the first garnet-type oxide solid electrolytes 1 and 2 increase significantly. Moreover, the experimental results show that when the heating temperature is 1100 °C, the ionic conductivity of the first garnet-type oxide solid electrolyte 1 (about 4.5×10 -4 S / cm) and the ionic conductivity of the first garnet-type oxide solid electrolyte 2 (about 3.5×10 -4 S / cm) are significantly higher than the ionic conductivity of the first garnet-type oxide solid electrolyte 3 (about 1.0×10 -4 S / cm).

[0090] The first garnet-type oxide solid electrolytes 1 and 2 are the first garnet-type oxide solid electrolytes manufactured using LLZO powders with median particle sizes (D50) of 0.1 μm and 0.1 μm, respectively. On the other hand, the first garnet-type oxide solid electrolytes 3 and 4 are the first garnet-type oxide solid electrolytes fabricated using LLZO powders with median particle sizes (D50) of 1 μm and 10 μm, respectively. Here, according to Figure 1 and Figure 2, for the first garnet-type oxide solid electrolytes 1 and 2, the influence of the heating temperature on the ionic conductivity is different when the cooling time is 4 hours (4 hours or more) and 1 hour (1 hour or less). More specifically, when the heating temperature is 1000 °C or higher, the ionic conductivity of the first garnet-type oxide solid electrolytes 1 and 2 decreases when the cooling time is 4 hours (4 hours or more), and increases when the cooling time is 1 hour (1 hour or less). In particular, when the heating temperature is 1100 °C, the ionic conductivity of the first garnet-type oxide solid electrolytes 1 and 2 is significantly lower than that of the first garnet-type oxide solid electrolyte 3 when the cooling time is 4 hours (4 hours or more), and significantly higher when the cooling time is 1 hour (1 hour or less). Thus, the experimental results suggest that when the heating temperature is 1050 - 1150 °C and the cooling time to room temperature is within 1 hour, the first garnet-type oxide solid electrolyte made of LLZO powder with a median particle size (D50) of 0.02 - 0.2 μm has a significantly higher ionic conductivity than the first garnet-type oxide solid electrolyte made of LLZO powder with a median particle size (D50) of 1 μm or more.

Claims

1. A method for manufacturing a garnet-type oxide solid electrolyte, wherein, Pressurize and form Li7La3Zr2O powder with a median particle size (D50) of 0.02 - 0.2 μm to obtain an intermediate product, 12 ​ The intermediate is heated at 1050 - 1150 °C for 1 - 3 hours, and then cooled to room temperature within 1 hour to obtain a first garnet-type oxide solid electrolyte.

2. The manufacturing method of the garnet-type oxide solid electrolyte according to claim 1, wherein, At least one selected from organic ionic plastic crystals and ionic liquids is brought into contact with the first garnet-type oxide solid electrolyte to obtain a second garnet-type oxide solid electrolyte.

3. The method for manufacturing a garnet-type oxide solid electrolyte according to claim 1 or 2, wherein, Pressurize and form the Li7La3Zr2O 12 powder under conditions of 72 MPa or higher to obtain the intermediate product.

Citation Information

Patent Citations

  • Interface layer of solid-state battery and manufacturing method thereof

    JP2020205284A